PARASITE COMMUNITIES OF TROPICAL FOREST RODENTS: INFLUENCES OF MICROHABITAT STRUCTURE AND SPECIALIZATION - Winker, Ashley M. (My University, 2013)
Parasitism is the most common life style and has important implications for the ecology and evolution of hosts. Most organisms host multiple species of parasites, and parasite communities are frequently influenced by the degree of host specialization. Parasite communities are also influenced by their habitat ? both the host itself and the habitat that the host occupies. Tropical forest rodents are ideal for examining hypotheses relating parasite community composition to host habitat and host specialization. Proechimys semispinosus and Hoplomys gymnurus are morphologically-similar echimyid rodents; however, P. semispinosus is more generalized, occupying a wider range of habitats. I predicted that P. semispinosus hosts a broader range of parasite species that are less host-specific than does H. gymnurus and that parasite communities of P. semispinosus are related to microhabitat structure, host density, and season. During two dry and wet seasons, individuals of the two rodent species were trapped along streams in central Panama to compare their parasites, and P. semispinosus was sampled on six plots of varying microhabitat structure in contiguous lowland forest to compare parasite loads to microhabitat structure. Such structure was quantified by measuring thirteen microhabitat variables, and dimensions were reduced to a smaller subset using factor analysis to define overall structure. Ectoparasites were collected from each individual, and blood smears were obtained to screen for filarial worms and trypanosomes. In support of my prediction, the habitat generalist (P. semispinosus) hosted more individual fleas, mites, and microfilaria; contrary to my prediction, the habitat specialist (H. gymnurus) hosted more individual lice, ticks, and species of ticks. Also contrary to my prediction, none of the tick species found on P. semispinosus were host-specific. The sole flea species I collected was Polygenis klagesi, which may be host-specific largely to P. semispinosus, only rarely infesting other mammals. Fleas were associated with forest openness with respect to trees and were more abundant during the rainy season. Lice were more abundant during the dry season, and ticks were more abundant on male hosts. Male-biased parasitism is common in mammals and presumably results from greater mobility and lower immune response than females. This descriptive study is the first to investigate the relationships between parasite communities and microhabitat, host density, and season in a lowland Neotropical forest. It lays the foundation for an experimental approach to study the interactions of these hosts and their parasites.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science-Biology
Keywords: Mammals - parasites; Host-parasite relationships; Parasitism; Rodents